The Application of the Social Ecological Model in Dilans Indonesia’s Social Media Campaigns - Elfryda Amelia Dhamayanti; Yuliani Rachma Putri (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2026)
This research aims to explore how the social ecological model is applied by Dilans Indonesia in social media campaigns. The presence of Dilans Indonesia, as one of the organizations in Indonesia dedicated to empowering individuals with disabilities and the elderly to become self-reliant members of society while advocating for their rightful entitlements from the government, serves as a crucial initiative in this regard. The initiative of the establishment of Dilans Indonesia was triggered by the reality faced by persons with disabilities and the elderly remain far from inclusive. This study employs a qualitative research method with a case study approach, analyzed through data processing using NVivo software. The study’s findings indicate that the campaign activities conducted by Dilans Indonesia through its social media channels, within the framework of social marketing indicates the relevance with the multi-level ecological model approach in promoting an inclusive culture for persons with disabilities and the elderly. The multi-level approach of the ecological model highlights the importance of influence at various levels of society. Through its efforts, Dilans Indonesia is expected to serve as a vanguard in accelerating the realization of an inclusive culture in Indonesia.